Kajian Dinamika Epidemi HIV Melalui Peran Populasi Kunci, Sebaran Geografis, dan Determinan Sosial untuk Intervensi yang Efektif - Aditya Setiawan (Mandalika Institute, 2026)
HIV/AIDS remains one of the major global health challenges with a high prevalence rate in many countries, including Indonesia. HIV transmission is closely related to behavioral factors, social stigma, and limited access to healthcare services. This study aims to analyze the implications of HIV/AIDS for transmission prevention strategies, including medical approaches, education, and community-based interventions. The findings indicate that the success of HIV transmission prevention is strongly influenced by public understanding, the availability of antiretroviral therapy (ART), and social support for People Living with HIV/AIDS (PLWHA). Therefore, prevention efforts must involve continuous education, universal access to ART, and the reduction of stigma and discrimination.